2013
DOI: 10.1186/2050-7771-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of a 35 kDa fragment of inter-alpha-trypsin inhibitor H4 in sera of healthy pregnant women and patients with hydatidiform mole

Abstract: BackgroundAccumulated data from previous studies appear to suggest a link between the overexpression of a 35 kDa fragment of serum inter-alpha-trypsin inhibitor H4 (ITIH4) with cancers that are associated with up-regulated levels of oestrogens. The truncated fragment was postulated to be a product of oestrogen-induced action of kallikrein on native ITIH4. The present lectin-based proteomic analyses were performed to assess the specificity of the 35 kDa fragment of ITIH4 as a potential cancer biomarker and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…APP including serum amyloid A, haptoglobin, alpha-1-acid glycoprotein, alpha-1-proteinase inhibitor (alpha-1-antitrypsin) and ITIH4 have been shown to increase in different inflammatory processes, in both in vivo and in vitro models, and involved several inflammatory diseases, such as Crohn’s disease and ulcerative colitis [ 39 – 41 ]. ITIH4 protein is a 120KD glycoprotein, which is prone to be cleaved to produce fragments of different length, such as 100 kDa and 35 kDa fragment, which have been identified as the biomarkers for Down syndrome [ 41 ], amyotrophic lateral sclerosis [ 42 ], and cancer [ 43 ]. A report showed that all heifers responded to the mastitis with increased ITIH4 concentrations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…APP including serum amyloid A, haptoglobin, alpha-1-acid glycoprotein, alpha-1-proteinase inhibitor (alpha-1-antitrypsin) and ITIH4 have been shown to increase in different inflammatory processes, in both in vivo and in vitro models, and involved several inflammatory diseases, such as Crohn’s disease and ulcerative colitis [ 39 – 41 ]. ITIH4 protein is a 120KD glycoprotein, which is prone to be cleaved to produce fragments of different length, such as 100 kDa and 35 kDa fragment, which have been identified as the biomarkers for Down syndrome [ 41 ], amyotrophic lateral sclerosis [ 42 ], and cancer [ 43 ]. A report showed that all heifers responded to the mastitis with increased ITIH4 concentrations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several methods, including lectin affinity chromatography [ 21 ] and lectin blotting [ 22 , 23 ], have earlier been used in studies identifying the composition of O- glycosylated proteins in sample fractions. However, these methods require substantial glycoprotein samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the high level of STAT3 expression in the luminal epithelium and stromal cells during pre-implantation period might be essential for establishing uterine receptivity [15]. ITI-H4 is the only member of the ITI family which harbors a kallikrein-released bradykinin-like domain in its C-terminal sequence, making its plasma kallikrein sensitive [16]. The cleaved form detected in the various subjects with enhanced estrogen levels may contribute to increased cleavage of ITI-H4 by elevating levels of circulating kallikrein in the serum [16].…”
Section: Introductionmentioning
confidence: 99%
“…ITI-H4 is the only member of the ITI family which harbors a kallikrein-released bradykinin-like domain in its C-terminal sequence, making its plasma kallikrein sensitive [16]. The cleaved form detected in the various subjects with enhanced estrogen levels may contribute to increased cleavage of ITI-H4 by elevating levels of circulating kallikrein in the serum [16]. In addition, plasma kallikrein is known to be expressed in hormone-dependent tissues such as the breast and ovary [17].…”
Section: Introductionmentioning
confidence: 99%